Surgery for constipation: systematic review and practice recommendations: Graded practice and future research recommendations. (29th September 2017) - Knowles, C. H.; Grossi, U.; Horrocks, E. J.; Pares, D.; Vollebregt, P. F.; Chapman, M.; Brown, S.; Mercer‐Jones, M.; Williams, A. B.; Yiannakou, Y.; Hooper, R. J.; Stevens, N.; et al.
Abstract: Aim: This manuscript forms the final of seven that address the surgical management of chronic constipation (CC) in adults. The content coalesces results from the five systematic reviews that precede it and of the European Consensus process to derive graded practice recommendations (GPR). Methods: Summary of review data, development of GPR and future research recommendations as outlined in detail in the 'introduction and methods' paper. Results: The overall quality of data in the five reviews was poor with 113/156(72.4%) of included studies providing only level IV evidence and only four included level I RCTs. Coalescence of data from the five procedural classes revealed that few firm conclusions could be drawn regarding procedural choice or patient selection: no single procedure dominated in addressing dynamic structural abnormalities of the anorectum and pelvic floor with each having similar overall efficacy. Of one hundred 'prototype' GPRs developed by the clinical guideline group, 85/100 were deemed 'appropriate' based on the independent scoring of a panel of 18 European experts and use of RAND‐UCLA consensus methodology. The remaining 15 were all deemed uncertain. Future research recommendations included some potential RCTs but also a strong emphasis on delivery of large multinational high‐quality prospective cohort studies. Conclusion: While the evidence base for surgery in CC is poor, the widespread European consensus for GPRs is encouraging. Professional bodies have the opportunity to build on this work by supporting the efforts of their membership to help convert the documented recommendations into clinical guidelines.